Diversity of culturable gut bacteria associated with the field populations of cotton leafhopper (Amrasca biguttula biguttula) in India - SIVAKUMAR, G; RANGESHWARAN, R; YANDIGERI, M S; MOHAN, M; VENKATESAN, T; VERGHESE, ABRAHAM (The Indian Journal of Agricultural Sciences, 2016)
Field populations of cotton leafhopper [Amrasca biguttula biguttula (Ishida)] exposed to heavy applications of imidacloprid, acephate, acetamiprid and dimethoate were collected from the seven cotton (Gossypium spp ) growing areas of the country. Thirty culturable bacteria were isolated from the guts of 16 populations of leafhoppers and were characterized through morphological and molecular methods. A good diversity of microflora was recorded across the location and is unique with respect to the locations. None of them are repeated except the genera Bacillus and Enterobacter. There was more number of gut microflora associated with the leafhoppers collected from Dharwad where the insecticide usage pattern and the number of sprays were very high as compared to other locations. Various Bacillus spp. were reported in the Dharwad population. The association of Enterococcus asburiae, Enterobacter silesiacus from the guts of leafhoppers of Guntur which was exposed to nine rounds of sprays of acephate, imidacloprid and dimethoate as compared to Bangalore which was not exposed to insecticides at all. Enterococcus hormaechei was isolated from the insects of Bangalore. The predominant bacterial genera identified in A.biguttula biguttula were Serratia, Bacillus, Enterococcus, Enterobacter, Pantoea, Methylobacterium, Stenotrophomonas, Pseudomonas and Paenibacillus.